Multipotent Stromal Stem Cells from Human Placenta Demonstrate High Therapeutic Potential - Nazarov, Igor (AlphaMed Press, 2012)
We describe human chorionic mesenchymal stem cell (hCMSC) lines obtained from the chorion of human term placenta with high therapeutic potential in human organ pathology. hCMSCs propagated for more than 100 doublings without a decrease in telomere length and with no telomerase activity. Cells were highly positive for the embryonic stem cell markers OCT-4, NANOG, SSEA-3, and TRA-1–60. In vitro, cells could be differentiated into neuron-like cells (ectoderm), adipocytes, osteoblasts, endothelial-like cells (mesoderm), and hepatocytes (endoderm)—derivatives of all three germ layers. hCMSCs effectively facilitated repair of injured epithelium as demonstrated in an ex vivo-perfused human lung preparation injured by Escherichia coli endotoxin and in in vitro human lung epithelial cultures. We conclude that the chorion of human term placenta is an abundant source of multipotent stem cells that are promising candidates for cell-based therapies.